Presença de nitrogênio amoniacal nas águas brutas afluentes às etas brasileiras e sua ameaça à segurança da água: estudos de caso - Dantas, Angela Di Bernardo; Di Bernardo, Luiz; Silva, Gabriela Mazocco Pereira da; Stancari, Rafaela Arantes; da Conceição, Natalia Ribeiro; Killer, Natalia Aparecida (International Workshop for Innovation in Safe Drinking Water, 2022)
In addition to ensuring that the treated water meets the standards required by legislation, it is essential that it be safe for human consumption. The increase in ammoniacal nitrogen concentrations in raw water is worrisome in Brazil due to the preservation conditions of the water sources, since the discharge of untreated sewage and/or industrial effluents is still a reality in the country. Besides contributing to the insertion of pathogenic microorganisms, in general, these effluents have increased concentrations of ammoniacal nitrogen, a compound that reduces the chlorine disinfection potential, widely used disinfectant in water treatment and, therefore, it can jeopardize the water microbiological safety. Thus, it is indispensable that the breakpoint chlorination be ensured to eliminate ammoniacal nitrogen and combined chlorine from the water.